2017
DOI: 10.1177/1071100716688198
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Correlates of Subtle Syndesmotic Injury

Abstract: The findings challenge the previously used but unsupported standard of a 2-mm diastasis of the tibiofibular articulation for diagnosis of subtle syndesmotic instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…In a study of 7 cadaveric specimens, Watson et al 21 found that ankle arthroscopy allowed the detection of syndesmotic instability when the AITFL and IOL were injured, especially in the sagittal and rotational planes. Guyton et al 10 evaluated 10 cadaveric specimens and found that, under a manual external rotation stress test, it was possible to detect rotational plane syndesmotic instability when 2 syndesmotic ligaments were cut (ie, AITFL and IOL). Less clarity exists, however, regarding which kind of ligamentous ankle injuries produce instability in the coronal plane when assessed arthroscopically using a standardized 100-N lateral hook test.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 7 cadaveric specimens, Watson et al 21 found that ankle arthroscopy allowed the detection of syndesmotic instability when the AITFL and IOL were injured, especially in the sagittal and rotational planes. Guyton et al 10 evaluated 10 cadaveric specimens and found that, under a manual external rotation stress test, it was possible to detect rotational plane syndesmotic instability when 2 syndesmotic ligaments were cut (ie, AITFL and IOL). Less clarity exists, however, regarding which kind of ligamentous ankle injuries produce instability in the coronal plane when assessed arthroscopically using a standardized 100-N lateral hook test.…”
Section: Discussionmentioning
confidence: 99%
“…They found that after sectioning both the AITFL and IOL that a 3-mm probe could be passed into the tibiofibular space in all 10 specimens, thus indicating syndesmotic instability, and concluded that this distance was highly predictive of injury to these 2 ligaments. 20 Evaluation of the IOM diastasis in our study revealed a measurement of >3.5 mm in 58% of specimens.…”
Section: Discussionmentioning
confidence: 49%
“…Work by Guyton et al 20 attempted to quantify syndesmotic disruption arthroscopically using a standardized measurement device (an arthroscopic spherical probe) to detect syndesmotic instability. In their cadaveric study, they sequentially sectioned the component parts of the syndesmosis and performed arthroscopy with manual external rotation stress testing in intact states and after each sequential sectioning of the AITFL, IOL, PITFL, and deltoid ligaments.…”
Section: Discussionmentioning
confidence: 99%
“…Diastasis of the syndesmosis can be shown by passage of the arthroscopic shaver through the syndesmosis. 17 Sagittal-plane instability of the syndesmosis can be shown by pushing the lateral malleolus anteriorly and posteriorly ( Fig 4 ).
Fig 4 Arthroscopically assisted reduction of sagittal-plane disruption of distal tibiofibular syndesmosis of the left ankle.
…”
Section: Techniquementioning
confidence: 99%
“…The interosseous ligament is a few millimeters above the ankle joint line and usually cannot be visualized by ankle arthroscopy. Diastasis of the syndesmosis can be shown by passage of the arthroscopic shaver through the syndesmosis 17 . Sagittal-plane instability of the syndesmosis can be shown by pushing the lateral malleolus anteriorly and posteriorly (Fig 4).…”
Section: Techniquementioning
confidence: 99%